Mind Control Training dan Mental Toughness: An Experimental Study of Female Basketball Athletes - Agustina, Dwi Nita; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Indonesian Journal of Sport Management, 2025)
Background: Basketball athletes often experience great mental pressure caused by various factors. The pressure faced is in the form of social pressure, performance expectations, and emotional factors that can affect mental toughness. This causes athletes to fail to improve concentration and mind control. Therefore, if athletes cannot control and control their own minds, it will greatly affect the mental toughness of athletes when they are in a match. Methods: The experimental method for 7 weeks was used in this study involving 13 female basketball athletes from Bandung Regency. The instrument used in the study was the Sport Mental Training Questionnaire (SMTQ). Data analysis was carried out by data processing using the t-test. Results: The results of the study showed that there was a significant effect of mind control training on the mental toughness of female basketball athletes. The results also showed an increase in the mental toughness of female basketball athletes between before and after receiving treatment by 18.5%. Implications and Recommendation: This study concludes that mind control training can be used as one method to improve the mental toughness of female basketball athletes. It is recommended for coaches to integrate this mind control training into athlete training programs so that athletes not only become better physically and technically, but also gain strong mental toughness.